Preparation method of magnetic microspheres capable of adsorbing heavy metals

By preparing the oxygen oxygenne loading aniline and tetraxyl hydroxymine aluminate, and modified with the hydroxylhhexylite, combined with amino acid ionic liquid and surface active agent to prepare a magnetic micro -ball with high adsorption capacity can be adsorbed There are problems that have small metal ions adsorption capacity and the problem of secondary pollution, which can achieve efficient and renewable heavy metal ion adsorption effects.

CN119327415APending Publication Date: 2025-01-21NINGBO FOTILE KITCHEN WARE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310880447.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, when removing heavy metal ions of composite pollutants in water bodies, there are problems such as small adsorption capacity, poor material selectivity, difficulty in regeneration and possible secondary pollution.

Method used

By preparing the oxygen oxygenne loading aniline and tetraxyl hydroxytine aluminate, and modified with the hydroxylhhexylite, combined with amino acid ionic liquid and surface active agent to prepare a magnetic micro -ball with high adsorption capacity.

Benefits of technology

It significantly improves the adsorption capacity and effect of heavy metal ions, ensure the renewability of the material and the characteristics of unlimited pollution, while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The preparation method of the magnetic microspheres capable of adsorbing the heavy metals is characterized by comprising the following steps: (1) loading aniline and tetrahydroxy sodium aluminate on graphene oxide; (2) preparing modified hydroxyapatite; (3) preparing magnetic microspheres; (4) preparing surface active macromonomer activated magnetic microspheres; compared with the prior art, the preparation method has the advantages that the aniline and the tetrahydroxy sodium aluminate are loaded on the graphene oxide, the hydroxyapatite is modified, and then the amino acid ionic liquid and the surface active macromonomer are used for modification to prepare the novel magnetic microspheres capable of adsorbing the heavy metals, so that the problem of heavy metal pollution is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of liquid filtration, and in particular to a method for preparing magnetic microspheres capable of adsorbing heavy metals. Background Art

[0002] With the further acceleration of the industrialization process, various enterprises have an increasing demand for heavy metals, and inevitably discharge a large amount of complex pollutants into the environment, such as heavy metal ions Cd 2+ , Pb 2+ These heavy metal ions not only seriously pollute surface water and groundwater, causing a sharp decline in global available water resources, but also increase the content of heavy metals in the soil, endangering the ecological environment and human health.

[0003] In recent years, the removal of complex pollutants in water has become a research hotspot in the process of water environment management. The removal methods of complex pollutants in water usually include: precipitation method, membrane separation technology, ion exchange resin, adsorption method, etc.

[0004] The precipitation method refers to using a certain mass of precipitant items to convert heavy metal ions in the wastewater solution into precipitates. However, the slag volume of the precipitate generated by the precipitation method is relatively high, and the precipitate needs to be post-treated. In addition, the pH value has a great influence on the precipitation, and the effect is unstable.

[0005] Membrane separation technology usually refers to the use of external force to make the solution pass through a selective semipermeable membrane to achieve separation of solvent and solution. Commonly used membrane separation technologies mainly include: ultrafiltration, nanofiltration, reverse osmosis, microfiltration, etc., but the manufacturing of semipermeable membranes is expensive, the cost is high and the stability is poor.

[0006] Ion exchange resin refers to a substance with active groups on the ion exchange resin that react with heavy metals. This type of group can form a chelate effect with heavy metal ions, thereby achieving the purpose of removing heavy metal ions. However, ion exchange resins are relatively expensive and tend to produce a certain amount of wastewater during regeneration, which can easily cause secondary pollution.

[0007] As a simple and efficient method, adsorption has attracted more and more attention from scholars. The adsorption method can deeply treat low-concentration heavy metal wastewater. The treated effluent has high water quality, strong operability and is economical and effective. However, traditional adsorption materials such as zeolite, quartz sand, lignin, chitosan, cellulose, etc. have problems such as poor selectivity, difficult regeneration, and adsorption of adsorbents limited by size. For example, the Chinese invention patent "Magnetic cross-linked chitosan-polyethyleneimine / biochar composite gel particles and preparation method" with application publication number CN115337912A cross-links chitosan and polyethyleneimine with a cross-linking agent and adds magnetic particles, biochar particles and porogens. After mixing evenly, it is added to the alkali solution to precipitate a black hydrogel, which is then washed with clean water to neutralize and then dried into solid particles. The cross-linked chitosan-polyethyleneimine encapsulates the magnetic particles and biochar particles to obtain a magnetic composite material. The magnetic composite material prepared by the invention has a synergistic adsorption effect on various heavy metal ions and azo dyes in water, and is recyclable and has no secondary pollution. However, due to the use of chitosan, the adsorption of the adsorbate of the magnetic composite material is limited by size, resulting in a small adsorption capacity. Summary of the invention

[0008] The technical problem to be solved by the present invention is to provide a method for preparing magnetic microspheres with high adsorption capacity and capable of adsorbing heavy metals in view of the above technical status.

[0009] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing magnetic microspheres capable of adsorbing heavy metals, characterized in that it comprises the following steps:

[0010] ① Graphene oxide loaded with aniline and sodium tetrahydroxyaluminate: Graphene oxide (GO) was placed in deionized water, and sodium persulfate and hydrochloric acid were added to obtain reaction solution A;

[0011] Aniline is dissolved in carbon tetrachloride (tetrachloroethane or bromoform may also be used), and then sodium tetrahydroxyaluminate is added to obtain reaction solution B;

[0012] The reaction solution A and the reaction solution B are mixed, reacted, filtered to obtain a solid product, and the solid product is washed and dried to obtain GO / PAN / Al;

[0013] ② Modified hydroxyapatite: Dissolve hydroxyapatite in acetic acid (triethyl phosphate or anhydrous ethanol) solution, add the GO / PAN / Al, add a catalyst under nitrogen atmosphere, add a cross-linking agent, stir, remove the supernatant after the reaction, and then wash and dry to obtain CHAP-GO / PAN / Al;

[0014] ③ Preparation of magnetic microspheres: adding amino acids to a hydrochloric acid solution (or phosphoric acid or sulfurous acid) and then adding deionized water, after the amino acids are completely dissolved, adding the CHAP-GO / PAN / Al and Tween 80, stirring to obtain a product, and then washing and drying the product to obtain magnetic microspheres;

[0015] ④ Preparation of magnetic microspheres capable of adsorbing heavy metals: adding the magnetic microspheres to a binary solvent, adding surfactants in sequence while stirring continuously, stirring, removing the supernatant after the reaction is completed, washing and drying to obtain magnetic microspheres capable of adsorbing heavy metals.

[0016] Unmodified hydroxyapatite can be dissolved in dilute acid solutions, such as hydrochloric acid, nitric acid and other inorganic acids and acetic acid and other organic acids, and unmodified hydroxyapatite has weak adsorption performance for heavy metals, especially low-concentration heavy metal wastewater. At the same time, hydroxyapatite has a low specific surface area and low adsorption capacity. Modification of hydroxyapatite increases its adsorption effect.

[0017] Preferably, the weight ratio of graphene oxide, sodium persulfate and sodium tetrahydroxyaluminate in step ① is 2-4:1-3:30-50.

[0018] Preferably, in step ①, the volume ratio of aniline to carbon tetrachloride is 1-2:2-3.

[0019] Preferably, in step ②, the weight ratio of hydroxyapatite to GO / PAN / Al is 10-20:2-3.

[0020] Preferably, in step ③, the weight ratio of amino acid, CHAP-GO / PAN / Al and Tween 80 is 3-5:1-2:1-2.

[0021] Preferably, in step ④, the weight ratio of the magnetic microspheres to the surfactant is 2-3:1-2.

[0022] Preferably, the catalyst in step ② is a mixture of one or more of ammonium persulfate, sodium bisulfate and triethanolamine.

[0023] Preferably, the cross-linking agent is a mixture of one or more of epichlorohydrin, propionaldehyde and citric acid.

[0024] Preferably, the amino acid in step ③ is a mixture of one or more of alanine (Ala), aspartic acid and glutamic acid.

[0025] Preferably, the binary solvent in step ④ is at least one of dioxane and butanol, o-dichlorobenzene and anhydrous ethanol, dichloromethane and dioxane.

[0026] Preferably, the surfactant is a mixture of one or more of allyl polyoxyethylene ether, alkylphenol polyvinyl ether (meth)acrylate, alkylphenol polyoxyethylene ether allyl ether, and alkyl alcohol polyoxyethylene ether allyl ether.

[0027] Preferably, in step ①, the particle size of graphene oxide is 120-200 nm, the purity is greater than 99%, and the thickness is 0.5-1.2 nm.

[0028] Preferably, the surface active macromolecular monomer activated magnetic microspheres prepared in step ④ have a thickness of 500-600 nm, a particle size range of 150-300 nm, and a pore size of 1.2-2.4 nm.

[0029] The preparation of magnetic microspheres capable of adsorbing heavy metals can be specifically carried out using the following technical contents: comprising the following steps:

[0030] (1) Weigh 0.2-0.4g of graphene oxide (GO) and place it in 20-30ml of deionized water. Slowly add 0.1-0.3g of sodium persulfate and 2-4ml of hydrochloric acid under constant stirring. In another container, weigh 10-20ml of aniline and dissolve it in 20-30ml of carbon tetrachloride. Then add 3-5g of sodium tetrahydroxyaluminate and stir it for 30-40min. Then pour it into the container with graphene oxide and react for 1-2h. After the reaction is completed, filter to obtain a solid product. Wash the solid product with 20ml of anhydrous ethanol for 30s and then dry it in an oven at 40℃ for 5h to obtain GO / PAN / Al.

[0031] (2) 2-4 g of hydroxyapatite was dissolved in 20-30 ml of acetic acid solution, 0.4-0.6 g of GO / PAN / Al was added under continuous stirring, 0.1-0.2 g of catalyst was added under nitrogen atmosphere, and then 0.2-0.4 g of cross-linking agent was added. The mixture was stirred at 40 °C for 40-50 min. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s and then dried in an oven at 40 °C for 5 h to obtain CHAP-GO / PAN / Al.

[0032] (3) Weigh 3-5 g of amino acid and add it to 10-20 ml of 40% hydrochloric acid solution, then add 50-60 ml of deionized water. After the amino acid is completely dissolved, add 1-2 g of CHAP-GO / PAN / Al and 1-2 g of Tween 80, and stir continuously for 30-40 min to obtain the product. The product is washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40 ° C for 5 h to obtain magnetic microspheres.

[0033] (4) Add 2-3 g of magnetic microspheres to 20-40 ml of binary solvent, add 1-2 g of surfactant macromolecular monomer in sequence while stirring continuously, stir at 70° C. for 1-2 h, remove the supernatant after the reaction is completed, wash the product with 20 ml of anhydrous ethanol for 30 s, and then dry it in an oven at 40° C. for 5 h to obtain magnetic microspheres activated by surfactant macromolecular monomers that can adsorb heavy metals.

[0034] Compared with the prior art, the advantages of the present invention are:

[0035] Hydroxyapatite has the ability to adsorb heavy metals, but the adsorption capacity of unmodified hydroxyapatite is not high. The surface of graphene oxide contains a large number of oxygen-containing functional groups, and its specific surface area is large, which provides a large number of adsorption sites for the adsorption of heavy metals. However, its fragile structure, easy destruction of the pore structure and difficulty in reuse limit its use. After modifying graphene oxide with aniline and sodium tetrahydroxyaluminate, its specific surface area and pore size can be increased, and more adsorption sites can be added. Combined with hydroxyapatite, it can effectively improve the effect of adsorbing heavy metals and increase the adsorption capacity.

[0036] After GO / PAN / Al is modified with amino acid ionic liquid, the problem of GO / PAN / Al dissolution can be effectively solved because amino acids have a strong hydrogen bond network structure. At the same time, amino acid molecules contain amino and carboxyl groups, which can have a certain effect of adsorbing heavy metals. Surfactants can activate the groups on the surface of magnetic microspheres that adsorb heavy metals, so that more groups can be exposed, and they can be effectively adsorbed even in solutions with very low heavy metal concentrations.

[0037] The preparation method of magnetic microspheres capable of adsorbing heavy metals has a simple process, mild conditions, and is easy to control. The raw materials used are all non-toxic or low-toxic raw materials. The raw material consumption during the reaction is small, the cost is low, and no toxic by-products are generated. It is an environmentally friendly synthesis method. The magnetic microspheres have a high content of functional groups and maintain good morphology and strength. They have broad application prospects in functional textiles, water and air purification, and chemical separation and extraction. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below with reference to the embodiments.

[0039] Example 1

[0040] (1) Weigh 0.2g of graphene oxide (GO) and place it in 20ml of deionized water. Slowly add 0.1g of sodium persulfate and 2ml of hydrochloric acid under constant stirring. In another container, weigh 10ml of aniline and dissolve it in 20ml of carbon tetrachloride. Then add 3g of sodium tetrahydroxyaluminate and stir it for 30min. Then pour it into the container with graphene oxide and react for 1h. After the reaction is completed, filter to obtain a solid product. Wash the solid product with 20ml of anhydrous ethanol for 30s and then dry it in an oven at 40℃ for 5h to obtain GO / PAN / Al.

[0041] (2) 2 g of hydroxyapatite was dissolved in 20 ml of acetic acid solution, and 0.4 g of GO / PAN / Al was added under continuous stirring. 0.1 g of triethanolamine was added under nitrogen atmosphere, and then 0.2 g of citric acid was added. The mixture was stirred at 40 °C for 40 min. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s and then dried in an oven at 40 °C for 5 h to obtain CHAP-GO / PAN / Al.

[0042] (3) Weigh 3 g of aspartic acid and add it to 10 ml of 40% hydrochloric acid solution, then add 50 ml of deionized water. After the amino acid is completely dissolved, add 1 g of CHAP-GO / PAN / Al and 1 g of Tween 80. Stir continuously for 30 min to obtain the product. Wash the product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 °C for 5 h to obtain magnetic microspheres.

[0043] (4) 2 g of magnetic microspheres were added to a binary solvent consisting of 10 ml of dioxane and 10 ml of butanol, and 1 g of allyl polyoxyethylene ether was added in sequence while stirring continuously. The mixture was stirred at 70°C for 1 h. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40°C for 5 h to obtain magnetic microspheres activated by surface active macromolecular monomers.

[0044] Example 2

[0045] (1) Weigh 0.3 g of graphene oxide (GO) and place it in 25 ml of deionized water. Slowly add 0.2 g of sodium persulfate and 3 ml of hydrochloric acid under constant stirring. In another container, weigh 15 ml of aniline and dissolve it in 25 ml of carbon tetrachloride. Then add 4 g of sodium tetrahydroxyaluminate and stir continuously for 35 min. Then pour it into the container containing graphene oxide and react for 1.5 h. After the reaction is completed, filter to obtain a solid product. Wash the solid product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 ° C for 5 h to obtain GO / PAN / Al.

[0046] (2) 3 g of hydroxyapatite was dissolved in 25 ml of acetic acid solution, and 0.5 g of GO / PAN / Al was added under continuous stirring. 0.15 g of triethanolamine was added under nitrogen atmosphere, and then 0.3 g of citric acid was added. The mixture was stirred at 40 °C for 45 min. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s and then dried in an oven at 40 °C for 5 h to obtain CHAP-GO / PAN / Al.

[0047] (3) Weigh 4 g of aspartic acid and add it to 15 ml of 40% hydrochloric acid solution, then add 55 ml of deionized water. After the amino acid is completely dissolved, add 1.5 g of CHAP-GO / PAN / Al and 1.5 g of Tween 80. Stir continuously for 35 min to obtain the product. Wash the product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 °C for 5 h to obtain magnetic microspheres.

[0048] (4) 2.5 g of magnetic microspheres were added to a binary solvent consisting of 15 ml of dioxane and 15 ml of butanol, and 1.5 g of allyl polyoxyethylene ether was added in sequence while stirring continuously. The mixture was stirred at 70 °C for 1.5 h. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40 °C for 5 h to obtain magnetic microspheres activated by surface active macromolecular monomers.

[0049] Example 3

[0050] (1) Weigh 0.4 g of graphene oxide (GO) and place it in 30 ml of deionized water. Slowly add 0.3 g of sodium persulfate and 4 ml of hydrochloric acid under constant stirring. In another container, weigh 20 ml of aniline and dissolve it in 30 ml of carbon tetrachloride. Then add 5 g of sodium tetrahydroxyaluminate and stir it for 40 min. Then pour it into the container containing graphene oxide and react for 2 h. After the reaction is completed, filter to obtain a solid product. Wash the solid product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 ° C for 5 h to obtain GO / PAN / Al.

[0051] (2) 4 g of hydroxyapatite was dissolved in 30 ml of acetic acid solution, and 0.6 g of GO / PAN / Al was added under continuous stirring. 0.2 g of triethanolamine was added under nitrogen atmosphere, and then 0.4 g of citric acid was added. The mixture was stirred at 40 °C for 50 min. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s and then dried in an oven at 40 °C for 5 h to obtain CHAP-GO / PAN / Al.

[0052] (3) Weigh 5 g of aspartic acid and add it to 20 ml of 40% hydrochloric acid solution, then add 60 ml of deionized water. After the amino acid is completely dissolved, add 2 g of CHAP-GO / PAN / Al and 2 g of Tween 80. Stir continuously for 40 min to obtain the product. Wash the product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 °C for 5 h to obtain magnetic microspheres.

[0053] (4) 3 g of magnetic microspheres were added to a binary solvent consisting of 20 ml of dioxane and 20 ml of butanol, and 2 g of allyl polyoxyethylene ether were added in sequence while stirring continuously. The mixture was stirred at 70 °C for 2 h. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s and then dried in an oven at 40 °C for 5 h to obtain magnetic microspheres activated by surface active macromolecular monomers.

[0054] Comparative Example 1: Graphene oxide is not modified with aniline and sodium tetrahydroxyaluminate

[0055] (1) 4 g of hydroxyapatite was dissolved in 30 ml of acetic acid solution, 0.6 g of GO was added under constant stirring, 0.2 g of triethanolamine was added under nitrogen atmosphere, and 0.4 g of citric acid was added, and the mixture was stirred at 40°C for 50 min. After the reaction, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40°C for 5 h to obtain CHAP-GO. 5 g of aspartic acid was weighed and added to 20 ml of 40% hydrochloric acid solution, and then 60 ml of deionized water was added. After the amino acid was completely dissolved, 2 g of CHAP-GO and 2 g of Tween 80 were added, and the mixture was stirred for 40 min to obtain the product. The product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40°C for 5 h to obtain magnetic microspheres.

[0056] (2) 3 g of magnetic microspheres were added to a binary solvent consisting of 20 ml of dioxane and 20 ml of butanol, and 2 g of allyl polyoxyethylene ether were added in sequence while stirring continuously. The mixture was stirred at 70°C for 2 h. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40°C for 5 h to obtain magnetic microspheres activated by surface active macromolecular monomers.

[0057] Comparative Example 2 Different Amino Acid Modification

[0058] (1) Weigh 0.4 g of graphene oxide (GO) and place it in 30 ml of deionized water. Slowly add 0.3 g of sodium persulfate and 4 ml of hydrochloric acid under constant stirring. In another container, weigh 20 ml of aniline and dissolve it in 30 ml of carbon tetrachloride. Then add 5 g of sodium tetrahydroxyaluminate and stir it for 40 min. Then pour it into the container containing graphene oxide and react for 2 h. After the reaction is completed, filter to obtain a solid product. Wash the solid product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 ° C for 5 h to obtain GO / PAN / Al.

[0059] (2) 4 g of hydroxyapatite was dissolved in 30 ml of acetic acid solution, and 0.6 g of GO / PAN / Al was added under continuous stirring. 0.2 g of triethanolamine was added under nitrogen atmosphere, and then 0.4 g of citric acid was added. The mixture was stirred at 40 °C for 50 min. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s and then dried in an oven at 40 °C for 5 h to obtain CHAP-GO / PAN / Al.

[0060] (3) 3 g of magnetic microspheres were added to a binary solvent consisting of 20 ml of dioxane and 20 ml of butanol, and 2 g of allyl polyoxyethylene ether were added in sequence while stirring continuously. The mixture was stirred at 70 °C for 2 h. After the reaction was completed, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40 °C for 5 h to obtain magnetic microspheres activated by surface active macromolecular monomers.

[0061] Comparative Example 3: No modification of surface active macromolecules

[0062] (1) Weigh 0.4 g of graphene oxide (GO) and place it in 30 ml of deionized water. Slowly add 0.3 g of sodium persulfate and 4 ml of hydrochloric acid under constant stirring. In another container, weigh 20 ml of aniline and dissolve it in 30 ml of carbon tetrachloride. Then add 5 g of sodium tetrahydroxyaluminate and stir it for 40 min. Then pour it into the container containing graphene oxide and react for 2 h. After the reaction is completed, filter to obtain a solid product. Wash the solid product with 20 ml of anhydrous ethanol for 30 s and then dry it in an oven at 40 ° C for 5 h to obtain GO / PAN / Al.

[0063] (2) 4 g of hydroxyapatite was dissolved in 30 ml of acetic acid solution, and 0.6 g of GO / PAN / Al was added under continuous stirring. 0.2 g of triethanolamine was added under nitrogen atmosphere, and then 0.4 g of citric acid was added. The mixture was stirred at 40 °C for 50 min. After the reaction, the supernatant was removed, and the product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40 °C for 5 h to obtain CHAP-GO / PAN / Al. 5 g of aspartic acid was weighed and added to 20 ml of 40% hydrochloric acid solution, and then 60 ml of deionized water was added. After the amino acid was completely dissolved, 2 g of CHAP-GO / PAN / Al and 2 g of Tween 80 were added, and the mixture was stirred for 40 min to obtain the product. The product was washed with 20 ml of anhydrous ethanol for 30 s, and then dried in an oven at 40 °C for 5 h to obtain magnetic microspheres.

[0064] The results of heavy metal adsorption experiments on the magnetic microspheres prepared in Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1:

[0065] The test method is as follows: 5g of magnetic microspheres are placed in a 100mL Cd 2+ and Pb 2+ The concentration of heavy metal ions in the solution was prepared to be 300 mg / L, and the pH value of the solution was 7.2. Three parallel samples were set for all experiments, and then placed under constant temperature shaking (25°C, 150rpm) for reaction, and samples were taken and analyzed at regular intervals. The calculation formula for the saturated adsorption amount is as follows:

[0066]

[0067] Where Qe is the saturated adsorption capacity of magnetic microspheres (mg*g ~1 );

[0068] C0 is the initial concentration of heavy metals in the solution (mg*L ~1 );

[0069] C1 is the concentration of heavy metal ions in the solution after adsorption equilibrium (mg*L ~1 );

[0070] V is the volume of the solution;

[0071] M is the dosage of adsorbent (mg)

[0072] Table 1

[0073] Saturated adsorption capacity Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Cd 2+ ]]> 164.6 168.3 172.4 74.2 96.1 82.4 <![CDATA[Pb 2+ ]]> 166.4 167.5 173.2 62.5 82.8 89.2

[0074] It can be seen from Table 1 that the magnetic microspheres prepared by the preparation method of the magnetic microspheres capable of adsorbing heavy metals of the present invention have a higher saturation adsorption capacity and a better adsorption effect on heavy metals.

[0075] The above is an exemplary description of the present invention. Obviously, the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various non-substantial improvements are made by using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly used in other occasions without further improvement, they are all within the protection scope of the present invention. The protection scope of the present invention shall be based on the protection scope defined in the claims.

Claims

1. A method for preparing magnetic microspheres capable of adsorbing heavy metals, characterized in that: The following steps are involved: ① Graphene oxide loaded with aniline and sodium tetrahydroxyaluminate: graphene oxide is placed in deionized water, and sodium persulfate and hydrochloric acid are added to obtain reaction solution A; Dissolving aniline in a first organic solvent, and then adding sodium tetrahydroxyaluminate to obtain a reaction solution B; The reaction solution A and the reaction solution B are mixed, reacted, filtered to obtain a solid product, and the solid product is washed and dried to obtain GO / PAN / Al; ② Modified hydroxyapatite: dissolve hydroxyapatite in a second organic solvent, add the GO / PAN / Al, add a catalyst under a nitrogen atmosphere, add a cross-linking agent, stir, remove the supernatant after the reaction, and then wash and dry to obtain CHAP-GO / PAN / Al; ③ Preparation of magnetic microspheres: adding amino acids to an inorganic acid solution, and then adding deionized water, after the amino acids are completely dissolved, adding the CHAP-GO / PAN / Al and Tween 80, stirring to obtain a product, and then washing and drying the product to obtain magnetic microspheres; ④ Preparation of magnetic microspheres capable of adsorbing heavy metals: adding the magnetic microspheres to a binary solvent, adding surfactants in sequence while stirring continuously, stirring, removing the supernatant after the reaction is completed, washing and drying to obtain magnetic microspheres capable of adsorbing heavy metals.

2. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The weight ratio of graphene oxide, sodium persulfate and sodium tetrahydroxyaluminate in step ① is 2-4:1-3:30-50.

3. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: In the step ①, the volume ratio of aniline to carbon tetrachloride is 1-2:2-3.

4. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: In the step ②, the weight ratio of hydroxyapatite to GO / PAN / Al is 10-20:2-3.

5. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: In the step ③, the weight ratio of amino acid, CHAP-GO / PAN / Al and Tween 80 is 3-5:1-2:1-2.

6. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: In the step ④, the weight ratio of the magnetic microspheres to the surfactant is 2-3:1-2.

7. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The catalyst in step ② is a mixture of one or more of ammonium persulfate, sodium bisulfate and triethanolamine.

8. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The cross-linking agent is a mixture of one or more of epichlorohydrin, propionaldehyde and citric acid.

9. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The amino acid in step ③ is a mixture of one or more of alanine, aspartic acid and glutamic acid.

10. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The binary solvent in step ④ is at least one of dioxane and butanol, o-dichlorobenzene and anhydrous ethanol, dichloromethane and dioxane.

11. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The surfactant is a mixture of one or more of allyl polyoxyethylene ether, alkylphenol polyvinyl ether (meth) acrylate, alkylphenol polyoxyethylene ether allyl ether, and alkyl alcohol polyoxyethylene ether allyl ether.

12. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: In the step ①, the particle size of graphene oxide is 120-200 nm, the purity is greater than 99%, and the thickness is 0.5-1.2 nm.

13. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The surface active macromolecular monomer activated magnetic microspheres prepared in step ④ have a thickness of 500-600 nm, a particle size range of 150-300 nm, and a pore size of 1.2-2.4 nm.

14. The method for preparing magnetic microspheres capable of adsorbing heavy metals according to claim 1, characterized in that: The first organic solvent is at least one of carbon tetrachloride, tetrachloroethane and bromoform; the second organic solvent is at least one of acetic acid, triethyl phosphate and anhydrous ethanol; the inorganic acid is at least one of hydrochloric acid, phosphoric acid and sulfurous acid.

Citation Information

Patent Citations

  • Magnetic cross-linked chitosan-polyethyleneimine / charcoal composite gel particle and preparation method thereof

    CN115337912A